Analysis Determinant Factors of Use Behavior of the Hospital Management Information System (HIS) with Behavioral Intention as Mediation at General Hospital Dr. Iskak Tulungagung - Agus Wahyudi; Ratna Wardani; Sri Suhandiah (Universitas STRADA Indonesia, 2025)
Background: The basis of this research problem comes from the importance of understanding the factors that influence the use of Hospital Management Information Systems (HIS). The adoption of HIS has direct implications for the operational efficiency and quality of health services provided by hospitals. Purpose: This research is to analyze the influence of Performance Expectancy, Effort Expectation and Social Influence on Use Behavior of the Hospital Management Information System with Behavioral Intention as mediation. Methods: Quantitative observational research with a cross sectional approach. The total population is 650 respondents and the sample is 248 respondents taken using the Stratified Random Sampling technique. Results: The results of the Multiple Linear Regression analysis showed that with a p-value of 0.000, it was concluded that there was an influence of Performance Expectancy, Effort Expectation and Social Influence on the Behavioral Intention of the Hospital Management Information System with an influence size 80.1%. The p-value is 0.000, so it can be concluded that there is a partial influence of Behavioral Intention on Use Behavior of the Hospital Management Information System with an influence size 87.4%. Conclusion: Engaging in intensive training, utilizing support resources, and providing open questions and input during implementation can accelerate the adaptation of the Hospital Management Information System at Hospital, has had a positive impact on improving the quality of health services.